NATIONAL NARRATIVES IN SYSTEM OF KINDS OF HISTORIOGRAPHIC SOURCES - Sergey I. Malovichko (Вестник Северо-Кавказского федерального университета, 2022)
In a paper raises the question of the specific features of the national history, occurred in the classical model of European historiography, the specific characteristic of kind of historiographic source as a national narrative is defined. The author clarifies the concept «socially oriented historical writing», analyzes the properties of national narrative as a kind of historiographic sources.